ANALISIS STRATEGI BERSAING TELKOM DALAM INDUSTRI INTERNET - , Endi Fitri Herlianto ([Yogyakarta] : Universitas Gadjah Mada, 2011)
In the future, the development of Indonesian society will be towards the information society where people use telecommunications as a strategic resource in conducting their daily activities. Internet as a telecommunications medium that provides tripleplay services (voice, image and data) will experience a high increase in demand to support and fit the present and future lifestyle Internet users in Indonesia will increase significantly. The fact shows that the growth of Internet users for the last 10 years increased by 1400% from 2 million users in 2000 to 30 million users in 2010. Telkom as one of internet service providers have a wireline based product called Telkom Speedy. This product must compete with similar products from competitors. Since there are 11 telecom providers in Indonesia, the competition is very intense (hypercompetition). Determining an appropriate competitive strategy for Telkom to face competition in the Internet industry is the goal of this research. The strategy formulation begins with an analysis of the external environment using PETS and 5 Forces model Porter. In line with that process an internal environmental analysis is also conducted using the SWOT model and the outcome will be used as the consideration in formulating appropriate competitive strategies using competitive strategy model, Porter (1980) and an additional strategy developed by Treacy and Wiserma (1997).